Bing's Sticky Plaster - HarperCollins Children's Books (London : HarperCollinsPublishers Ltd, 2023)
A great new Bing picture book about how all kids want to have plasters, whether they need one or not, based on the award-winning CBeebies show.
TV tie-in
Keywords: Bing (Fictitious character) -- Juvenile fiction; Bing (Fictitious character); Children's stories; Children's stories Pictorial works